2013
DOI: 10.1016/j.devcel.2013.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin Regulation by BAF170 Controls Cerebral Cortical Size and Thickness

Abstract: Increased cortical size is essential to the enhanced intellectual capacity of primates during mammalian evolution. The mechanisms that control cortical size are largely unknown. Here, we show that mammalian BAF170, a subunit of the chromatin remodeling complex mSWI/SNF, is an intrinsic factor that controls cortical size. We find that conditional deletion of BAF170 promotes indirect neurogenesis by increasing the pool of intermediate progenitors (IPs) and results in an enlarged cortex, whereas cortex-specific B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
234
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(248 citation statements)
references
References 41 publications
11
234
2
1
Order By: Relevance
“…23,26,27 Conversely, little BAF170 is expressed in stem/progenitor cells (e.g., embryonic stem cells, or ESCs) and at higher levels in differentiated cells (e.g., neurons). 23,26,27 We hypothesized that although only low expression levels are detected for BAF170 in proliferating ESCs and for BAF155 in post-mitotic neurons, this expression is necessary and sufficient to stabilize the embryonic stem cell (es) BAF and neuronal (n)BAF complexes. Indeed, when we derived ESC lines from blastocysts and primary neurons from forebrains (both representing the dcKO_CAG-Cre genotype), we found that the depletion of BAF155 and BAF170 in these cultured cells led to the loss of BAF subunit expression at the protein level.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…23,26,27 Conversely, little BAF170 is expressed in stem/progenitor cells (e.g., embryonic stem cells, or ESCs) and at higher levels in differentiated cells (e.g., neurons). 23,26,27 We hypothesized that although only low expression levels are detected for BAF170 in proliferating ESCs and for BAF155 in post-mitotic neurons, this expression is necessary and sufficient to stabilize the embryonic stem cell (es) BAF and neuronal (n)BAF complexes. Indeed, when we derived ESC lines from blastocysts and primary neurons from forebrains (both representing the dcKO_CAG-Cre genotype), we found that the depletion of BAF155 and BAF170 in these cultured cells led to the loss of BAF subunit expression at the protein level.…”
Section: Resultsmentioning
confidence: 99%
“…23,28 However, when we examined epigenetic marks in cortex-specific dcKO_Emx1-Cre mice, which lacked entire BAF complexes, we observed a global reduction in euchromatin along with increased H3K27me2/3 and decreased H3K9Ac in the developing cortex during both embryonic and perinatal stages, as assessed by assays such as ChIP-Seq, immunohistochemistry, and western blotting. 21 Thus, our data showed for the first time that the presence of BAF complexes is needed to maintain the balance between global repression and local activation of epigenetic programs during cortical development.…”
Section: The Loss Of Baf Complexes Induces the Accumulation Of H3k27mmentioning
confidence: 92%
“…Both of these genes are expressed in the thalamus (Allen Brain Atlas: http://human.brain-map.org; Braineac: http://www.braineac.org/ (Ramasamy et al, 2014)), and Chip-seq data in mouse brain has suggested that their homologues (H2-K1 and Znrd1) are regulated by the transcriptional factor Pax6 (Xie et al, 2013), a major actor in the developing central nervous system. Notably Pax6 interacts with Baf150 and Baf177 to regulate cerebral size and thickness (Tuoc et al, 2013;Xie et al, 2013). Furthermore, both HLA-A and ZNRD1 contain SNPs associated with schizophrenia by GWAS; rs2524005 is intronic in HLA-A (Bergen et al, 2012) and rs8321 is in the 3 0 untranslated region of ZNRD1 (Cross-Disorder Group of the Psychiatric Genomics Consortium, 2013b).…”
Section: Discussionmentioning
confidence: 99%
“…BAF170 has been found to be an intrinsic factor that controls cortical size. Conditional deletion of Baf170 was found to promote indirect neurogenesis by increasing the pool of intermediate progenitors and in turn result in an enlarged cortex (34). Similarly, overexpression of Baf170 promoted direct neurogenesis and resulted in the development of a smaller cortex.…”
Section: What Is Arid1b?mentioning
confidence: 91%